An Overview of Perioperative Care for Pediatric Patients. (25th June 2016) - Derieg, Sarah
Abstract: Care of pediatric surgical patients is not limited to pediatric facilities, and all perioperative RNs should have a basic understanding of the specialized care that children require. This knowledge set includes an understanding of the basic terminology used to describe this patient population as well as the developmental stages of pediatric patients. Preoperatively, the nurse should conduct a thorough assessment and evaluation and address the anxieties and questions of the patient and his or her parent or guardian. Intraoperatively, the nurse should be prepared to help manage difficult intubation, laryngospasm during induction and extubation, difficult IV access, positioning, skin care, surgical site preparation, and thermoregulation. Postoperative care considerations include addressing airway differences, vital signs, pain assessment and management, fluid management, and preparation for discharge. Awareness of the anatomic and physiologic differences, developmental stages, and surgical needs of children will allow the perioperative RN to provide high‐quality, safe care to the pediatric surgical patient.